2021
DOI: 10.1038/s41598-021-92569-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between orthorexia nervosa symptomatology and body image attitudes and distortion

Abstract: Orthorexia Nervosa (ON), a condition characterized by a fixation on healthy eating, still does not conform to any consensus concerning diagnostic criteria, notably in regard to a possible body image component. This study investigated the relationship between ON symptomatology, measured with the Eating Habit Questionnaire, and body image attitudes and body image distortion in a non-clinical sample. Explicit body image attitudes and distortion were measured using the Multidimensional Body-Self Relations Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“… Individuals with ON may display implicit or explicit body image distortion [ 45 ]. Further research is needed to determine similarities and differences in body image issues across the eating disorder spectrum using a transdiagnostic model.…”
Section: Resultsmentioning
confidence: 99%
“… Individuals with ON may display implicit or explicit body image distortion [ 45 ]. Further research is needed to determine similarities and differences in body image issues across the eating disorder spectrum using a transdiagnostic model.…”
Section: Resultsmentioning
confidence: 99%
“…Tension-induced obsessive-compulsive disorder is also associated with distortions in body mass index (BI). Therefore, it is important to value and invest in a healthy body, exercise and proper weight control to develop a healthy and ideal BI (Pauzé et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, participants can be unaware of the criteria they adopt, because the RC approach allows them to make instantaneous and instinctive choices when selecting facial stimuli that more resemble their faces (see Brinkman et al, 2017 , for review). In addition, previous studies have suggested that mental representations visualized through the RC method are less affected by certain response patterns or social desirability than are self-reported measures (e.g., Moon et al, 2020 ; Pauzé et al, 2021 ). Likewise, our findings showed that social desirability was not significantly related to self-CIs but was to self-image relevant variables, such as explicit self-evaluation and self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…During the task, some participants may be unaware of the criteria that they adopt to select images ( Brinkman et al, 2017 ). Therefore, mental representations visualized through the RC method may be less susceptible to social desirability as compared to explicit measures, such as self-reports ( Pauzé et al, 2021 ). Supporting this argument, Moon et al (2020) reported that participants’ social desirability was not significantly associated with their self-CIs but with self-reported variables related to self-image.…”
Section: Introductionmentioning
confidence: 99%